Deres Temple: a hidden gem for optimizing social studies learning - Arif, Syarifuddin; Harmanto; Wisnu (Harmoni Sosial: Jurnal Pendidikan IPS, 2025)
Deres Temple is a historical testament to the journey of Majapahit in East Java. Although not as famous as the others, Deres Temple is a valuable investment for social science learning. Located in the Gumuk Mas sub-district, several schools serve as educational institutions. Deres Temple serves as empirical evidence for social science learning, particularly regarding kingdoms in the archipelago. As an effort to bridge theoretical concepts, Deres Temple’s existence is growing. The potential of Deres Temple is explored based on the spirit of intellectual values, which are integrated into discussions of student curiosity and the preservation of Deres Temple. With knowledge, teachers can explore Deres Temple’s potential as a teaching medium that is easily accessible to students. Deres Temple’s potential is explored for educational purposes. The subjects of this study were students of Gumuk Mas Junior High School. Thus, Deres Temple is very representative for exploring its potential to achieve learning objectives. This study used a descriptive qualitative approach. Data collection was carried out through participatory observation, interviews, and documentation. The data obtained were analyzed in three stages. More than 80% of the students involved showed active participation by asking questions related to Candi Deres. This paper contributes to the field by demonstrating how Deres Temple can be integrated as an accessible, context-based learning resource that enhances student curiosity and supports social science education through active engagement with local historical heritage.